Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.2147/cmar.s191047
|View full text |Cite
|
Sign up to set email alerts
|

<p>Postmastectomy radiotherapy using three different techniques: a retrospective evaluation of the incidental dose distribution in the internal mammary nodes</p>

Abstract: ObjectiveTo evaluate the incidental coverage dose to the internal mammary nodes (IMN) in patients treated with postmastectomy radiotherapy (PMRT) and its relationship with the treatment plan.Patients and methodsWe retrospectively analyzed 138 patients undergoing PMRT and divided them into three groups: three-dimensional conformal radiotherapy (3D-CRT), field-in-field forward intensity-modulated radiotherapy (F-IMRT), and inverse intensity-modulated radiotherapy (I-IMRT). The IMN were contoured according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Geometrical variations and inaccuracies during RNI are mostly related to patients positioning during radiotherapy and anatomical changes during the course of treatment. The suggested CTV to PTV margins for RNI in breast cancer vary between 5 mm and 10 mm [ 17 , 21 , 26 , 27 ]. However, the current literature lacks data and analyses regarding the PTV margins for modern treatment modalities such as VMAT or SIB irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Geometrical variations and inaccuracies during RNI are mostly related to patients positioning during radiotherapy and anatomical changes during the course of treatment. The suggested CTV to PTV margins for RNI in breast cancer vary between 5 mm and 10 mm [ 17 , 21 , 26 , 27 ]. However, the current literature lacks data and analyses regarding the PTV margins for modern treatment modalities such as VMAT or SIB irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…IMNI has been shown to have a significant impact on locoregional control, breast cancer mortality, and OS (5-7), but controversies concerning IMNI still exist, mainly because of radiotherapy-induced longterm lung and heart toxicity (8,24,25). Though the incidental dose to the IMNs not achieve clinically significant therapeutic levels (26,27), recent studies have demonstrated that accepting adequate doses during incidental irradiation can result in a clinical benefit (6,10). By determining the variability in the IIMNI dose coverage with standard chest wall tangential fields (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with breast cancer (stage I, II, or III), observed IMLN recurrence rate was < 1.5% after primary breast cancer treatment, even when the internal mammary chain (IMC) not excised or irradiated [11][12][13]. Patients most likely benefit from systemic therapies and incidental regional node irradiation [14][15][16][17][18]. But according to extended radical mastectomy data, 9.2% of patients with no positive axillary nodes (ALN) present IMLN metastasis [19].…”
Section: Introductionmentioning
confidence: 99%